Other chilhoods and adolescences in Maghrebi literature: the construction of homosexual identity in the works of Abdellah Taïa - Vidal-Luengo, Ana Ruth; Darias Marrero, Agustín; Casimiro Galván , Gema Lucía (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
Abdellah Taïa is one of the greatest exponents of the current Maghrebi novel of French expression, with a series of autobiographical stories in which he narrates the evolution of his homosexual identity. The present paper explores and compares different models of coming-of-age storytelling in contemporary Maghrebi literature, which may have influenced Taïa in his works: Mon Maroc (2000) and Une mélancolie arabe (2008). With the aim of observing the evolution of the Bildungsroman model in this literature, two tales of childhood and adolescence have been selected from Moroccan literature in Arabic: Fī-l-ṭufūla (In Childhood), by Abdelmayid Benyelloun ([1954] 1992), y al-Jubz al-ḥāfī (For Bread Alone) by Mohamed Choukri ([1982] 1993). These referents show stories of learning that start from the heteronormative autobiographical literary canon of modern Arab literature and evolve to relate other types of childhood and adolescence, which are part of the social reality of the Maghreb. This comparative analysis follows a threefold approach based on: family and affective-sexual relationships; cultural references as models of socio-cultural gender identity; and the construction of homosexual identity, as manifested in Taïa’s literary idiolect in a more or less implicit way, depending on the moment of his own trajectory.